Community-Acquired Respiratory Viruses - Gottlieb, Jens (Seminars in Respiratory and Critical Care Medicine, 2018)
The incidence of community-acquired respiratory viruses (CARVs) is ∼15 cases per 100 patient-years after lung transplantation (LTx). Paramyxoviruses account for almost 50% of the cases of CARV infection in LTx. Most patients will be symptomatic with a mean decline of 15 to 20% in forced expiratory volume in 1 second. The attributable death rate is low in recent years 15 to 25% CARV infected LTx patients will develop chronic lung allograft dysfunction within a year after CARV infection. This risk seems to be increased in comparison to the noninfected LTx recipient.Detection rate of CARV dependent on clinical awareness, sampling, and diagnostic method with nucleic acid testing by polymerase chain reaction in bronchoalveolar lavage is the gold standard after LTx.There is no approved treatment for paramyxoviruses, most centers use ribavirin by various routes. Toxicity of systemic ribavirin is of concern and some patients will have contraindication to this treatment modality. Treatment may reduce the risk to develop chronic lung allograft dysfunction and respiratory failure. Agents under development are inhibiting viral attachment and use silencing mechanisms of viral replication.
Keywords: lung transplantation; community-acquired respiratory viruses; ribavirin; bronchiolitis obliterns syndrome